FAKTOR-FAKTOR YANG MEMENGARUHI KEJADIAN GIZI BURUK PADA BALITA DIMASA PANDEMIK COVID-19 DI WILAYAH KERJA PUSKESMAS TAWANGA KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Alpin Alpin; Wa Ode Salma; Ramadhan Tosepu (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Research Objectives is to determine the factors that influencethe incidence of malnutrition in Toddlers during the Covid-19 Pandemic in the working area of the Tawanga Health Center, Konawe Regency, Southeast Sulawesi Province. This type of research is an observational analytic study withusing a cross sectional study design. The analysis used is univariate, bivariate and multivariate. The sampling technique used is simple random sampling with a sample size of 97 respondents. There is no effect between maternal education and the incidence of malnutrition in children under five(ρValue 0.596 >α = 0.05); There is an influence of mother's knowledge with the incidence of malnutrition in children under five (ρValue = 0.047 <α = 0.05); There is an influence of family income with the incidence of malnutrition in children under five(ρValue = 0.000 <α = 0.05); There is an influence of a history of infectious diseases affecting the incidence of malnutrition in children under five(ρValue = 0.016 <α = 0.05); There is an effect of parenting with the incidence of malnutrition in Toddlers (ρValue = 0.000 <α = 0.05); There is an effect of the number of family members with the incidence of malnutrition in children under five(ρValue = 0.001 <α = 0.05). The results of multivariate analysis showed that the most influential factors with the incidence of malnutrition include income with a significance value of Value 0.000, and the number of family members with a significance value of Value 0.051. There is an influence between knowledge, family income, mother's occupation, history of infectious diseases, parenting patterns and the number of family members with Malnutrition in Toddlers during the Covid-19 Pandemic in the working area of the Tawanga Health Center, Konawe Regency, Southeast Sulawesi Province so that Puskesmas as gate keeper needs to improve education through nutrition counseling programs, and maximize nutrition improvement programs with PMT for toddlers who have underweight nutritional status and increase early detection of groups at high risk of malnutrition.